Designing Indonesian tribal Song Content with a Lo-fi Music Approach Through the YouTube Application - Bayu Syahputra; Bryan Tandian (Universitas Internasional Batam, 2024)
This research aims to determine the influence of Indonesian tribal songs, which are made in a different genre from the original, considering that Indonesian tribal songs still need to be remembered. This research uses applied and qualitative methods, where the design of this tribal song uses the 4D method, and the analysis of the result making lo-fi tribal songs uses a qualitative approach. Data collection in designing song content uses questionnaires while analyzing the results of song creation uses interviews with the WhatsApp application. This research shows that it is beneficial in promoting tribal songs to the community, especially students.